Adjunct Faculty and NFL Referees: The Appropriation of Value from Professional Part‐Time Workers. Issue 3 (September 2015) - Lengermann, Patricia; Niebrugge, Gillian; Newfield, Marcia; Berry, Joe; Kroik, Polina
<x xml:space="preserve">Abstract</x> This article distinguishes a particular category of "part‐time worker"—the professional who works part‐time—and traces how such workers have the value of their professional skill appropriated by their employers. We do this by a comparison of the NFL Referees' Strike of 2012—NFL referees are part‐time employees—with the debate over whether adjunct faculty should be covered by the terms of the Affordable Care Act (ACA). These two seemingly disparate labor actions are joined in the analysis by the fact that both involved a series of textual constructions. These textual constructions are explored using sociologist Dorothy E. Smith's patterning of modern global capitalism as a system divided into "the local actualities of lived experience" where the world's work is done and "the extra‐local relations of ruling" where "texts" are created that pattern and appropriate that work. We consider the NFL Referees' Strike as a "teachable moment" when public attention was turned to a labor issue; we then question whether the debate over the ACA and adjunct faculty might serve the same purpose. We conclude that the diversity among adjunct faculty in terms of their financial and career relation to adjunct teaching—which contrasts with a uniformity among NFL referees—makes it hard to craft a unifying message. We end by suggesting that the relations of ruling are perhaps well served by the current lack of information about adjunct faculty, a lack that makes it hard for organizers to mobilize them.